The in vitro effects of Voghera sweet pepper on thyroid cancer cells: modulation of oxidative stress and pro-tumorigenic genes - Coperchini, Francesca; De Luca, Fabrizio; Greco, Alessia; Croce, Laura; Franchi, Elena; Teliti, Marsida; Pignatti, Patrizia; Magri, Flavia; Bottone, Maria Grazia; Rotondi, Mario (Frontiers in Nutrition, 2025)
BackgroundVoghera pepper (VP) extracts were demonstrated to have anti-oxidant ability in several cell types.PurposeThis study aimed to assess whether VP-extracts could lower oxidative stress and modulate thyroid cancer (TC) cells behavior in vitro.MethodsExtracts were analyzed using the LC-DAD-MS system. Thyroid cell lines, both normal (NHT) and cancerous (TPC-1 and 8505C) were treated with increasing concentrations of Yellow (YVP) and Green (GVP) VP-extracts over time. Viability and proliferation were assessed in all cell types. Changes in Reactive-oxygen-species (ROS) production by TPC-1 and 8505C were assessed by flow-cytometry. The mRNA expression of anti-oxidant mediators (NFE2L2, HMOX1, SOD2 and CAT), epithelial-to-mesenchymal transition markers (POU5F1, SNAI1, TWIST1, SNAI2 and VIM) and thyroid-differentiation-related genes (NKX2-1 and PAX8) were evaluated by RT-PCR.ResultsTreatment with GVP or YVP reduced the viability of TPC-1 and 8505C but not those of NHT, without effects on cells proliferation. GVP and YVP reduced basal and H2O2-induced ROS production in TC cells. GVP and YVP up-regulated mRNA levels of several anti-oxidant genes. GVP and YVP reduced mRNA of POU5F1 in TPC-1 and 8505C. Finally, the mRNA of PAX-8 was reduced by GVP and YVP extracts in TPC-1 and 8505C, while NKX2-1 was reduced by both GVP and YVP in TPC-1 and only by GVP exposure in 8505C.ConclusionThis is the first demonstration of the potential beneficial effects of VP extracts in TC in terms of reduction of oxidative stress, increase of antioxidant markers, and modulation of markers of metastasis and de-differentiation in TC cells.